Acute and subchronic 90-days toxicity assessment of propyl-propane-thiosulfinate (PTS) in rats. (March 2022) - Cascajosa-Lira, Antonio; Pichardo, Silvia; Baños, Alberto; Guillamón, Enrique; Molina-Hernández, Verónica; Moyano, Rosario; Jos, Ángeles; Cameán, Ana M
Abstract: The organosulfur compounds (OSC) extracted from Allium spp . exhibit antibacterial, antifungal, and antioxidant properties. The agri-food industry is taking advantage of these properties by using them as natural feed and food additives. In the present work, an acute and a subchronic 90-days toxicity studies have been conducted for the first time to assess the safety of the OSC propyl-propane-thiosulfinate (PTS). Both studies were carried out following the Organization for Economic Co-operation and Development test guidelines (425 and 408, respectively). The acute study provided a maximum tolerated dose (MTD) of 175 mg/kg and the subchronic study established the Non Observed Adverse Effect Level (NOAEL) ≥ 55 mg/kg body weight (b.w.)/day in both sexes. In addition, the subchronic study performed on rats exposed to 14, 28 and 55 mg/kg b.w./day PTS, revealed no changes in any of the hematological parameters measured as well as no differences in body weight and water/food consumption. However, biochemical parameters were altered in some groups, although they were not biologically significant (Ca 2+ in female rats, and the thyroids hormones T3 and T4 in rat males). Furthermore, the histopathological assessment evidenced no abnormality on the gastrointestinal, respiratory, lymphoid, urinary, circulatory, nervous, musculoskeletal, and reproductive systems.